FENOMENA FOMO YANG MENGAKIBATKAN MINAT BELI PRODUK KOSMETIK YANG DI-ENDORSE OLEH INFLUENCER MEDIA SOSIAL TERHADAP MAHASISWA DI INDONESIA - Jeni Putri Pramudiani; Farah Margaretha Leon (STMIK Widuri Jakarta, 2024)
This research aims to analyze the influence of Imitation of Influencer, Materialism, Social Comparison, , and Fear of Missing Out (FOMO) on Buying Intention. Data were collected through questionnaires from consumers who follow the social media accounts of five beauty influencers, namely Tasya Farasya, Nanda Arsyinta, Hanum Mega, Titan Tyra, and Kiara Leswara are domiciled in Jakarta. The study used a sample size of 166 respondents with purposive sampling technique. The data analysis method employed in this research is Structural Equation Model (SEM) using AMOS 21 software. The results indicate that Imitation of Influencer has a positive influence on Social Comparison, Imitation of Influencer has a positive influence on Materialism, Social Comparison does not have a positive influence on FOMO, FOMO has a positive influence on Buying Intention, Social Comparison does not have a positif influence on Materialism, and Materialism has a positive influence on Buying Intention.